11-Ketotestosterone is a major androgen produced in porcine adrenal glands and testes. Issue 210 (June 2021) - Yazawa, Takashi; Sato, Takahiro; Nemoto, Takahiro; Nagata, Sayaka; Imamichi, Yoshitaka; Kitano, Takeshi; Sekiguchi, Toshio; Uwada, Junsuke; Islam, Mohammad Sayful; Mikami, Daisuke; Nakajima, Ikuyo; Takahashi, Satoru; et al.
Highlights: Porcine preadipocytes differentiated into 11KT-producing steroidogenic cells. Porcine AKR1C1 can catalyze conversion of A4 and 11KA4 into T and 11KT. Porcine HSD11B2 is expressed in Leydig cells and adrenal cortex. 11KT is a dominant androgen especially in female porcine. 11KT can induce eNOS in porcine ECs. Abstract: Porcine steroid hormone profiles have some unique characteristics. We previously studied human and murine steroidogenesis using steroidogenic cells-derived from mesenchymal stem cells (MSCs). To investigate porcine steroidogenesis, we induced steroidogenic cells from porcine subcutaneous preadipocytes (PSPA cells), which originate from MSCs. Using cAMP, adenovirus-mediated introduction of steroidogenic factor-1 (SF-1)/adrenal 4-binding protein (Ad4BP) induced the differentiation of PSPA cells into sex steroid-producing cells. Introducing SF-1/Ad4BP also induced the aldo-keto reductase 1C1 (AKR1C1) gene. Porcine AKR1C1 had 17β-hydroxysteroid dehydrogenase activity, which converts androstenedione and 11-ketoandrostenedione into testosterone (T) and 11-ketotestosteorne (11KT). Furthermore, differentiated cells expressed hydroxysteroid 11β-dehydrogenase 2 (HSD11B2) and produced 11KT. HSD11B2 was expressed in testicular Leydig cells and the adrenal cortex. 11KT was present in the plasma of both immature male and female pigs, with slightly higher levels in the male pigs. T levels were much higher in the male pigs. It is noteworthy that in the female pigs, the 11KT levels were >10-fold higher than the T levels. However, castration altered the 11KT and T plasma profiles in the male pigs to near those of the females. 11KT induced endothelial nitric oxide synthase (eNOS) in porcine vascular endothelial cells. These results indicate that 11KT is produced in porcine adrenal glands and testes, and may regulate cardiovascular functions through eNOS expression.